Liability of shipowners and classification societies for environmental damage and unsafe working conditions at recycling yards. Issue 3 (17th July 2022) - Glinski, Carola
Abstract: This article deals with two liability issues that are highly relevant for value chain responsibility in the maritime sector, in particular for safe and environmentally sound recycling of ships: liability of shipowners and ship managers for unsafe downstream value chains for end‐of‐life ships and liability of classification societies in their role under the Ship Recycling Regulation. After an introduction to the current regime of ship recycling and its shortcomings, the article first elaborates on recent developments in value chain responsibility before it presents liability as an important regulatory tool. It then analyses relevant recent case law, including by the Court of Justice of the European Union and by national courts in France, Germany and the United Kingdom, showing that liability risks for shipowners and classification organizations have increased significantly, which may have a positive impact on environmentally sound and safe ship recycling. The article concludes, however, that a clear legislative framework for liability would be preferable to avoid uncertainty and national differences.